A Dialogue about the Emerging Market for New Credentials. Issue 189 (24th February 2020) - Gallagher, Sean; Maxwell, Nan
Abstract: This chapter focuses on the overall themes, priorities, and "calls to action" that emerged from a discussion and reflection among community college leaders on the chapters in this volume.